Estimating the risk of dengue transmission from Dutch blood donors travelling to Suriname and the Dutch Caribbean. Issue 4 (14th January 2016) - Oei, W.; Lieshout‐Krikke, R. W.; Kretzschmar, M. E.; Zaaijer, H. L.; Coutinho, R. A.; Eersel, M.; Jubithana, B.; Halabi, Y.; Gerstenbluth, I.; Maduro, E.; Tromp, M.; Janssen, M. P
Abstract : Background: The risk of dengue transmitted by travellers is known. Methods to estimate the transmission by transfusion (TT) risk from blood donors travelling to risk areas are available, for instance, the European Up‐Front Risk Assessment Tool (EUFRAT). This study aimed to validate the estimated risk from travelling donors obtained from EUFRAT. Methods: Surveillance data on notified dengue cases in Suriname and the Dutch Caribbean islands (Aruba, Curaçao, St. Maarten, Bonaire, St. Eustatius and Saba) in 2001–2011 was used to calculate local incidence rates. Information on travel and donation behaviour of Dutch donors was collected. With the EUFRAT model, the TT risks from Dutch travelling donors were calculated. Model estimates were compared with the number of infections in Dutch travellers found by laboratory tests in the Netherlands. Results: The expected cumulative number of donors becoming infected during travels to Suriname and the Dutch Caribbean from 2001 to 2011 was estimated at 5 (95% CI, 2–11) and 86 (45–179), respectively. The infection risk inferred from the laboratory‐based study was 19 (9–61) and 28 (14–92). Given the independence of the data sources, these estimates are remarkably close. The model estimated that 0·02 (0·001–0·06) and 0·40 (0·01–1·4) recipients would have been infected by these travelling donors. Conclusions: The EUFRAT model provided an estimate close to actual observed number of dengue infections. The dengue TT risk among Dutch travelling donors can be estimated using basic transmission, travel and donation information. The TT risk from Dutch donors travelling to Suriname and the Dutch Caribbean is small.